Postharvest treatments of fresh produce - Mahajan, P.; Caleb, O.; Singh, Zora; Watkins, C.; Geyer, M. (The Royal Society Publishing, 2014)
Postharvest technologies have allowed horticultural industries to meet the global demands of local and large-scale production and intercontinental distribution of fresh produce that have high nutritional and sensory quality. Harvested products are metabolically active, undergoing ripening and senescence processes that must be controlled to prolong postharvest quality. Inadequate management of these processes can result in major losses in nutritional and quality attributes, outbreaks of foodborne pathogens and financial loss for all players along the supply chain, from growers to consumers. Optimal postharvest treatments for fresh produce seek to slow down physiological processes of senescence and maturation, reduce/inhibit development of physiological disorders and minimize the risk of microbial growth and contamination. In addition to basic postharvest technologies of temperature management, an array of others have been developed including various physical (heat, irradiation and edible coatings), chemical (antimicrobials, antioxidants and anti-browning) and gaseous treatments. This article examines the current status on postharvest treatments of fresh produce and emerging technologies, such as plasma and ozone, that can be used to maintain quality, reduce losses and waste of fresh produce. It also highlights further research needed to increase our understanding of the dynamic response of fresh produce to various postharvest treatments.